Phosphinate analogs of D-, D-dipeptides: slow-binding inhibition and proteolysis protection of VanX, a D-, D-dipeptidase required for vancomycin resistance in Enterococcus faecium. - Wu, Z (1995)
VanX is a D-Ala-D-Ala dipeptidase that is essential for vancomycin resistance in Enterococcus faecium. Contrary to most proteases and peptidases, it prefers to hydrolyze the amino substrate but not the related kinetically and thermodynamically more favorable ester substrate D-Ala-D-lactate. The enzymatic activity of VanX was previously found to be inhibited by the phosphinate analogs of the proposed tetrahedral intermediate for hydrolysis of D-Ala-D-Ala. Here we report that such phosphinates are slow-binding inhibitors. D-3-[(1-Aminoethyl)phosphinyl]-D-2-methylpropionic acid I showed a time-dependent onset of inhibition of VanX and a time-dependent return to uninhibited steady-state rates upon dilution of the enzyme/inhibitor mixture. The initial inhibition constant Ki after immediate addition of VanX to phosphinate I to form the E-I complex is 1.5 microM but is then lowered by a relatively slow isomerization step to a second complex, E-I*, with a final K*i of 0.47 microM. This slow-binding inhibition reflects a Km/K*i ratio of 2900:1. The rate constant for the slow dissociation of complex E-I* is 0.24 min-1. A phosphinate analog with an ethyl group replacing what would be the side chain of the second D-alanyl residue in the normal tetrahedral adduct gives a K*i value of 90 nM. Partial proteolysis of VanX reveals two protease-sensitive loop regions that are protected by the intermediate analog phosphinate, indicating that they may be part of the VanX active site.